Immunosuppression variably impacts outcomes for patients hospitalized with COVID-19: A retrospective cohort study. - Vijeeth Guggilla; Jennifer A Pacheco; Alexandre M Carvalho; Grant R Whitmer; Anna E Pawlowski; Jodi L Johnson; Catherine A Gao; Chad J Achenbach; Theresa L Walunas (PLoS ONE)
Background Adults with immunosuppression are more likely to develop severe COVID-19 than adults without immunosuppression. Less is known about differences in outcomes for adults with immunosuppression who are hospitalized with COVID-19. Methods A retrospective cohort study of adults hospitalized with COVID-19 at Northwestern Medicine hospitals between 03/01/2020 and 05/31/2022 was performed. Regression analyses were performed comparing in-hospital mortality, intensive care unit (ICU) admission, oxygenation requirements, and hospital/ICU length of stay among patients without immunosuppression (n = 9079) and patients with immunosuppression (n = 873). Results Patients with immunosuppression had significantly higher mortality than patients without immunosuppression (OR: 1.33, 95% CI: 1.11-1.60). This effect was even stronger when controlling for age at admission, diabetes, obesity, SARS-CoV-2 variant era, and COVID-19 medication use (adjusted OR: 1.78, 95% CI: 1.46-2.16). ICU admission (adjusted OR: 1.64, 95% CI: 1.41-1.90) and invasive ventilation (adjusted OR: 1.68, 95% CI: 1.36-2.06) were also significantly higher in patients with immunosuppression. Hospitalization length (median: 7 days) and ICU length of stay (median: 2.5 days) were longer in patients with immunosuppression compared to patients without immunosuppression (median: 5 days, adjusted p < 0.001; median: 2 days, adjusted p = 0.04). Subgroup analyses showed that patients with solid organ transplant, HIV with low CD4 cell count, and secondary immunodeficiency had significantly higher adjusted mortality and ICU admission compared to patients without immunosuppression. Patients with solid organ transplant also had significantly higher invasive ventilation and ICU length of stay. Conclusions Patients with immunosuppression had worse outcomes than patients without immunosuppression. Subgroup analyses showed that patients with solid organ transplant had the worst outcomes overall. Patients with HIV had similar outcomes as patients without immunosuppression unless CD4 cell count was low.